Probiotics interventions modulating gut microbiota composition in individuals with intestinal constipation: Protocol of a systemic review and meta-analysis of randomized controlled trials - Zubing Mei; Peixin Du; Ye Han; Zhuo Shao; De Zheng (PLoS ONE, 2025)
Introduction Intestinal constipation is a substantive global health concern, significantly impairing patient quality of life. An emerging view is that the gut microbiota plays a critical role in intestinal function, and probiotics could offer therapeutic benefits. This study aims to consolidate evidence from randomized controlled trials (RCTs) that assess the effectiveness of probiotics in modulating microbiota and ameliorating symptoms of constipation. Methods We will execute a systematic evidence search across Medline (via PubMed), Embase, Cochrane CENTRAL, Web of Science, Scopus, and CINAHL, employing explicit search terms and further reference exploration. Two independent reviewers will ensure study selection and data integrity while assessing methodological quality via the Cochrane Collaboration’s Risk of Bias-2 tool. Our primary goal is to outline changes in microbiota composition, with secondary outcomes addressing symptom relief and stool characteristics. Meta-analyses will adopt a random-effects model to quantify the effects of interventions, supplemented by subgroup analyses and publication bias assessments to fortify the rigor of our findings. Discussion This study endeavors to provide a rigorous, synthesized overview of the probiotics interventions evidence for modulating gut microbiota in individuals with intestinal constipation. The insights derived could inform clinical guidelines, nurture the creation of novel constipation management strategies, and direct future research in this field. Ethics and dissemination As this study aggregates and analyzes existing data without direct human subject involvement, no ethical approval is required. We will disseminate the study’s findings through scientific forums and seek publication in well-regarded, peer-reviewed journals. Trial registration OSF registration number: 10.17605/OSF.IO/MEAHT.